In silico mapping of Conserved Ortholog Set (COS) markers in the potato genome. - Lindqvist-Kreuze, H.; Portal, L.; Rodríguez, F.; Simon, R.; Mueller, L.; Spooner, D.M.; Bonierbale, Merideth W. (2013)
Conserved ortholog set (COS) markers are useful for genetic mapping across diverse taxa, including the Solanaceae. We amplified over 300 COS markers from diverse set of Solanum germplasm, sequenced them and aligned into the whole genome sequence of potato. We also mapped a set of COS markers genetically using three diploid interspecific Solanum crosses. Comparisons between the physical and genetic location in potato and tomato confirm that most of the COS markers studied are single or low copy in the potato genome. The genomic locations are mostly in agreement between the maps, but there are some that map in unexpected locations. Sequence comparisons between different Solanum species show that some of these markers may be paralogs. The single copy markers that have unexpected locations between physical and genetic maps may be true differences as we are comparing different Solanum species (DM = phureja, BCT = berthaultii x tuberosum, PCC1 = paucissectum x chomatophilum, PD = phureja x tuberosum, and finally tomato). It is also possible that the potato reference sequence may contain small numbers of incorrectly oriented or misplaced scaffolds as well as genes that were not discovered by the gene prediction algorithm used. Further work focusing on the genome regions that from this work show contradictory results may facilitate the refinement of the genome assembly.